Analisis Sentimen Objek Wisata Bali Di Google Maps Menggunakan Algoritma Naive Bayes - Utami, Dian Siti; Erfina, Adhitia (STIKOM Tunas Bangsa Pematangsiantar, 2022)
Bali is one of the most popular tourist destinations in Indonesia because it has a variety of tourist attractions. So this study aims to analyze a tourist review on Google Maps of the most recommended tourist attractions in Bali. The author considers that the review can be used as a data by scrapping data from the Data Miner Website. Then the data that has been extracted is analyzed by predicting a rapid miner using the Naïve Bayes Algorithm, which is considered to have a high enough level of accuracy so that it can determine 5 recommended Bali tourist attractions based on tourist reviews on Google Maps. The results of this study conclude that Nusa Pedina with an accuracy value of 94.64% is the most visited Bali tourist attraction because the accuracy value is superior to Garuda Wisnu Kencana with an accuracy value of 82.86%, edge with an accuracy value of 80%, Pandawa with an accuracy value by 82.86%. The accuracy value is 90.71%, Uluwutu Temple with an accuracy value of 85.54%.